ESC Congress 2020, the digital experience: a report from the ESC Scientists of Tomorrow - Schmidt, Constanze; Bollini, Sveva (Cardiovascular research, 2020)
His inspiring presentation included a critical discussion on the main lifestyle factors (including sleep, stress, and diet) affecting atherosclerosis, systemic inflammatory networks, haematopoiesis, and gut metabolism.The ESC Gold Medals were awarded to exceptional researchers who have made an extraordinary contribution to cardiovascular medicine and science. This year, three gold medals were granted in the fields of clinical cardiology, population science and, for the first time, in basic science. The gold medal in clinical cardiology was awarded to Prof. John McMurray from the University of Glasgow (UK), an internationally distinguished leader in the field of heart failure (HF) treatment, co-ordinator of large clinical trials and author of healthcare guidelines for HF management. Prof. Kari Stefansson, founder and CEO of the Reykjavik-based deCODE genetics company in Iceland, was awarded the ESC Gold Medal in population science for his pioneering work on population-scale genetics of cardiological diseases such as atrial fibrillation (AF), hypertension and HFHe significantly contributed to characterizing genomic diversity of genes serving as drug targets. Finally, the ESC gold medal in basic science was awarded to Prof. Stefanie Dimmeler, director of the Institute of Cardiovascular Regeneration at the University of Frankfurt (Germany), in light of her remarkable contribution to research on cardiovascular regeneration and identifying non-coding RNAs as potential therapeutic tools for personalized medicine.